2013
DOI: 10.1016/j.bmc.2013.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic phosph(on)ate inhibitors of Plasmodium falciparum hypoxanthine-guanine-xanthine phosphoribosyltransferase

Abstract: The pathogenic protozoa responsible for malaria lack enzymes for the de novo synthesis of purines and rely on purine salvage from the host. In Plasmodium falciparum (Pf), hypoxanthine-guanine-xanthine phosphoribosyltransferase (HGXPRT) converts hypoxanthine to inosine monophosphate and is essential for purine salvage making the enzyme an anti-malarial drug target. We have synthesized a number of simple acyclic aza-C- nucleosides and shown that some are potent inhibitors of Pf HGXPRT while showing excellent sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…Thus, enzymes of the salvage pathway are identified as potential therapeutic targets against these parasites [1][2][3][4]. Therapeutic intervention that targets these enzymes requires development of effective analogues of the natural substrates and on-enzyme intermediates [5,6]. As a first step, a thorough understanding of the structure of the natural substrates and intermediates is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, enzymes of the salvage pathway are identified as potential therapeutic targets against these parasites [1][2][3][4]. Therapeutic intervention that targets these enzymes requires development of effective analogues of the natural substrates and on-enzyme intermediates [5,6]. As a first step, a thorough understanding of the structure of the natural substrates and intermediates is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Among various nitrogen‐containing nucleotides 8 – 10 obtained by Zhou, only analog 10 ( B = Gua) showed slight inhibitory activity against HSV‐1, HSV‐2, and CMV . Aza‐nucleotide 11 with nitrogen incorporated into the phosphonoalkyl residue and its N ‐branched derivative 12 appeared to be selective inhibitors of phosphoribosyltransferase P f HGXPRT, a key enzyme for the growth of Plasmodium falciparum , and at the same time did not show detectable inhibitory activity against human HGPRT. Moreover, it was shown that the protection of the amino functionalities in 13 with bulky groups such as tert ‐butoxycarbonyl (Boc) or benzoyl (Bz) leads to the enhancement of antiviral activities of the protected compounds .…”
Section: Introductionmentioning
confidence: 99%
“…122 Biological studies on Pf and human PRT enzymes revealed that CPME analogues were inactive, in agreement with the fact that a five-atom chain is optimal for tight interactions at the active site. 123,124 Concerning HPEP derivatives, again the nature of the nucleobase was found to be crucial as only the 8-bromoguanine, guanine and hypoxanthine analogues showed some affinity (with Ki in the low micromolar range), but only the guanine HPEP ANP presented a 6-fold better selectivity for the parasite enzyme. CPEE derivatives exhibited similar activities against both enzymes, and in this case only the hypoxanthine derivatives appeared to be more selective for Pf HGXPRT than for human HGPRT.…”
Section: Figure 19: Representatives Of Pmp Anpsmentioning
confidence: 99%